2016
DOI: 10.1093/jxb/erw290
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin LjGlb1-1 is involved in nodulation and regulates the level of nitric oxide in theLotus japonicus–Mesorhizobium lotisymbiosis

Abstract: HighlightMissense and null Lotus japonicus mutants allowed us to demonstrate that hemoglobin LjGlb1-1 is required for infection thread elongation and nodule formation, probably by regulating nitric oxide production in the roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 44 publications
4
54
0
Order By: Relevance
“…Specifically, Glb1-1 is induced by NO, whereas Glb1-2 and Glb2 are not (Shimoda et al, 2005;Bustos-Sanmamed et al, 2011). After only 4 h of inoculation with Mesorhizobium loti, the roots of L. japonicus produce a transient increase in NO concentration along with the induction of Glb1-1, whereas after infection with pathogenic bacteria the NO concentration remains high for at least 24 h (Shimoda et al, 2005;Nagata et al, 2008;Fukudome et al, 2016). These and other observations led the authors to propose that Glb1-1 acts as an NO scavenger at the early stage of rhizobial infection, thereby preventing the plant's defense response.…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, Glb1-1 is induced by NO, whereas Glb1-2 and Glb2 are not (Shimoda et al, 2005;Bustos-Sanmamed et al, 2011). After only 4 h of inoculation with Mesorhizobium loti, the roots of L. japonicus produce a transient increase in NO concentration along with the induction of Glb1-1, whereas after infection with pathogenic bacteria the NO concentration remains high for at least 24 h (Shimoda et al, 2005;Nagata et al, 2008;Fukudome et al, 2016). These and other observations led the authors to propose that Glb1-1 acts as an NO scavenger at the early stage of rhizobial infection, thereby preventing the plant's defense response.…”
Section: Introductionmentioning
confidence: 98%
“…The differences in CO binding kinetics found in this work, along with the large variations in O 2 affinities and expression profiles reported earlier (Sainz et al, 2013), strongly suggest that the three proteins perform non-redundant functions. Overexpression of LjGlb1-1 increases the symbiotic performance of L. japonicus (Shimoda et al, 2009) and, conversely, the knocked-out line shows alterations in the infection process and produces fewer nodules than the wild-type line (Fukudome et al, 2016). Consequently, transgenic approaches aimed at increasing the content of each of the three nsHbs, or of a combination of them, in the model legume L. japonicus (first stage) and in a crop legume with comparable nsHbs, such as soybean or common bean (second stage), are likely to result in outperformance of plants, at least under symbiotic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides leghemoglobins, whose expression is restricted to nodules, legumes contain nsHbs in leaves, roots, and nodules (Andersson et al, 1996; Bustos-Sanmamed et al, 2011). In fact, some of these nsHbs have important functions in the onset of symbiosis (Fukudome et al, 2016) and exhibit high expression in nodules compared with other plant organs (Bustos-Sanmamed et al, 2011). In this work, we have studied the nsHbs of Lotus japonicus , a model legume for classical and molecular genetics (Handberg and Stougaard, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, treatment of M. truncatula roots in interaction with S. meliloti with 1‐mM cPTIO inhibits nodulation as long as cPTIO is present in the medium (del Giudice et al, ), suggesting that NO is needed for symbiosis. In contrast, in the L. japonicus – Mesorhizobium loti symbiosis, the overexpression of Pgb LjHb1 (LjGlb1) or AfHb1 results in a decrease in NO level and an increase in nodule number (Shimoda et al, ), whereas L. japonicus lines mutated for LjGlb1 show higher NO production and lower infection and nodule number (Fukudome et al, ). Similarly, experiments carried out in peas ( Pisum sativum ) in symbiosis with Rhizobium leguminosarum show that 2‐mM sodium nitroprusside, a NO donor, affects the adhesion and the penetration of rhizobia in roots and that this effect is reversed by the addition of 2‐μM equine erythrocyte haemoglobin (Glyan'ko, Mitanova, & Vasil'eva, ).…”
Section: Does Soil N Status and No Influence Nodulation?mentioning
confidence: 99%
“…Cytochrome c oxidase (COX; Complex IV) and Complex III (bc 1 ) are the sites of NO production in ETC ( Figure 1). Inhibition of the Mitochondrial Complex III with myxothiazol and inhibition of Complex IV with KCN indeed lead to the abolishment of NO production in mitochondria (reviewed in Fukudome et al, 2016 Another NO biosynthetic pathway that has been shown to be involved in nodules is the NOS pathway. To date, no NOS-like gene or protein homologue for NOS have been identified in higher plants, but a gene named AtNOA1 (NO associated) and encoding a GTPase was characterized in Arabidopsis thaliana.…”
Section: No Sources During Symbiosis: Current Statusmentioning
confidence: 99%